2017
DOI: 10.21859/sija-1202192
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Perceived Social Support in the Elderly

Abstract: ObjectivesThe purpose of the study was to determine depression and perceived social support and some related factors among the elderly people in urban areas of Tehran in the area of Shahid Beheshti University of Medical Sciences. Methods & Materials A cross-sectional study was conducted with 580 elderly of Tehran in Shahid Beheshti University using a multistage systematic sampling method. Data were collected by trained questioners. Standard Beck depression, Zimet perceived social support and demographic questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 4 publications
3
20
1
Order By: Relevance
“…However, the concordance between the two studies may indicate the proximity of depressive disorder in the elderly in Zanjan and the use of appropriate scales for sampling and data analysis in the present study. Bakhtiari et al reported the overall prevalence of depression 51.87% so that in this study, the rate of mild, moderate, and severe depression was 17.41, 25.58, and 8.88%, respectively, which corroborates with the total depression of the present study [26], but the severity of depression is not consistent with the present study since the mean depression in this study is more than mild depression. Further, Beck's questionnaire was used to assess depression, but the GDS questionnaire in the current study may be the reason for the difference in these results.…”
Section: Discussionsupporting
confidence: 59%
“…However, the concordance between the two studies may indicate the proximity of depressive disorder in the elderly in Zanjan and the use of appropriate scales for sampling and data analysis in the present study. Bakhtiari et al reported the overall prevalence of depression 51.87% so that in this study, the rate of mild, moderate, and severe depression was 17.41, 25.58, and 8.88%, respectively, which corroborates with the total depression of the present study [26], but the severity of depression is not consistent with the present study since the mean depression in this study is more than mild depression. Further, Beck's questionnaire was used to assess depression, but the GDS questionnaire in the current study may be the reason for the difference in these results.…”
Section: Discussionsupporting
confidence: 59%
“…The questionnaire has 2 items which are scored using a 5-point Likert scale from "strongly disagree" to "strongly agree" (20,21). The Iranian version of this tool has been used in a domestic study among older people (22). The questionnaires were evaluated among 45 eligible participants in a pilot carried out before our study.…”
Section: Methodsmentioning
confidence: 99%
“…For many reasons, older adults are vulnerable to mental illness, and about 15%–25% of them have serious psychological problems. 2 …”
Section: Introductionmentioning
confidence: 99%